Planet Earth. The complete series [videorecording (DVD)]. - Attenborough, David, 1926- (British Broadcasting Corporation ; Warner Home Video [distributor], 2007)
A stunning 11-part series that captures rare action, impossible locations, and intimate moments with our planet's best-loved, wildest, and most elusive creatures.